P Perdamaian Dunia di Era Globalisasi dalam Perspektif Metafisis Alfred North Whitehead: World Peace in the Era of Globalization in the Metaphysical Perspective of Alfred North Whitehead - Sihombing, Yusuf Mario; Riyanto, FX. Eko Armada (Jurnal Filsafat Indonesia, 2024)
The  current  global  society  is  increasingly filled  with  various  complex  problems.  War,  the phenomenon of the "Double Effect of Modernity," poverty, world hunger, and even the global climate crisis has significantly exacerbated global conditions. This situation urges humanity to urgently rebuild the awareness of living together in the spirit of peace for the sake of human welfare itself. Peace becomes a very important value in building human life globally to avoid competitive and apathetic situations among nations. To explore the understanding of reality and existence amid the dynamics of the modern world, Alfred North Whitehead's metaphysical philosophy provides very helpful guidance for humans to introspect on the plurality of each individual's existence. Whitehead's concept of "Process and Reality" depicts reality as a series of continuously changing processes within a metaphysical unity. This understanding allows us to see peace as a result of the integration of humanity in a world of mutual dependence and interconnectedness. Moreover, religion inherently plays an important role in the effort to shape global peace by inspiring values such as justice and humanity. This research is qualitative. Using the literature study method, the author implements Whitehead's thoughts on the current concrete situation. Whitehead's metaphysical perspective opens up a viewpoint on peace as a unifying factor for the world holistically, particularly as an effort to face geopolitical challenges and global conflicts. The purpose of this research is to encourage public introspection on the importance of a harmonious awareness of collective life that implies a spirit of peace.